Extremely low wear rates in hip joint bearings coated with nanocrystalline diamond. (September 2015) - Amaral, M.; Maru, M.M.; Rodrigues, S.P.; Gouvêa, C.P.; Trommer, R.M.; Oliveira, F.J.; Achete, C.A.; Silva, R.F.
Abstract: A hip joint wear simulator is used for the first time to evaluate the performance of acetabular liners and femoral heads made of silicon nitride ceramic coated with nanocrystalline diamond (NCD), grown by a hot filament chemical vapor deposition (HFCVD) method. Wear is assessed by gravimetry, by which volume and linear wear are estimated. Even with only one million cycles of test, a very stimulating finding is the extremely low wear rate of the head after the diamond polishing running-in step, of about 0.005 mm 3 /million cycles (Mc). This corresponds to a linear wear of 0.08 μm/Mc, one order of magnitude better than the best value currently known for ceramic-on-ceramic hip joints. Small scale abrasion is found as the dominant wear mechanism. Highlights: Nanocrystalline diamond coated ceramic hip joints are evaluated in a wear simulator. Results of 1 million cycles of simulated wear test are presented for the first time. Very small volume wear of 0.005 mm 3 /million cycles results from small scale abrasion.